A Chitosan-based Hydrogel with PLCL, ZnO NPs, and Oligoelements: A Promising Antibiotic Scaffold for Tissue Engineering - Salinas Delgado, Yvain de los Ángeles; Soria Sánchez, Sthepanie; Esquivel Barajas, Gabriela Guadalupe; Leos Quiñonez, Eduardo; Bretado Aragón, Luis Alberto (Revista Mexicana de Ingenieria Biomedica, 2022)
Tissue engineering involves anchorage-dependent cells cultured on scaffolds, with growth factors added to facilitate cell proliferation. Its use in transplants implies the risk of bacterial infection. The current contribution describes the preparation and antibacterial evaluation of a chitosan-based hydrogel physically cross-linked with poly(l-lactic-co-ɛ-caprolactone) (PLCL) and enriched with zinc oxide nanoparticles (ZnO NPs) and trace elements (potassium and magnesium). The material was developed as a scaffold with built-in antibacterial properties. Chitosan and PLCL are biocompatible support materials applied in medicine for the repair and regeneration of damaged tissues, objectives promoted by ZnO NPs and the aforementioned trace elements. The ZnO NPs were elaborated by chemical coprecipitation. The materials were characterized by XRD, FT-IR, and SEM. Antibacterial testing was performed with strains of Escherichia coli and Staphylococcus aureus by the Kirby-Bauer method, in accordance with the NCCLS and CLSI guidelines. It was possible to obtain a homogeneous hydrogel with adequate morphology and distribution of elements. The hydrogel with 300 mM of Mg, K, and ZnO NP’s showed antibacterial inhibition halos of 13 mm for S. aureus and 19 mm for E. coli. This innovative biomaterial with trace elements holds promise for tissue engineering by considering the challenge of bacterial infection.